Atrazine chlorohydrolase from Pseudomonas sp. strain ADP: gene sequence, enzyme purification, and protein characterization. - de Souza, M L (1996)
Pseudomonas sp. strain ADP metabolizes atrazine to carbon dioxide and ammonia via the intermediate hydroxyatrazine. The genetic potential to produce hydroxyatrazine was previously attributed to a 1.9-kb AvaI DNA fragment from strain ADP (M. L. de Souza, L. P. Wackett, K. L. Boundy-Mills, R. T. Mandelbaum, and M. J. Sadowsky, Appl. Environ. Microbiol. 61:3373-3378, 1995). In this study, sequence analysis of the 1.9-kb AvaI fragment indicated that a single open reading frame, atzA, encoded an activity transforming atrazine to hydroxyatrazine. The open reading frame for the chlorohydrolase was determined by sequencing to be 1,419 nucleotides and encodes a 473-amino-acid protein with a predicted subunit molecular weight of 52,421. The deduced amino acid sequence matched the first 10 amino acids determined by protein microsequencing. The protein AtzA was purified to homogeneity by ammonium sulfate precipitation and anion-exchange chromatography. The subunit and holoenzyme molecular weights were 60,000 and 245,000 as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and gel filtration chromatography, respectively. The purified enzyme in H2(18)O yielded [18O]hydroxyatrazine, indicating that AtzA is a chlorohydrolase and not an oxygenase. The most related protein sequence in GenBank was that of TrzA, 41% identity, from Rhodococcus corallinus NRRL B-15444R. TrzA catalyzes the deamination of melamine and the dechlorination of deethylatrazine and desisopropylatrazine but is not active with atrazine. AtzA catalyzes the dechlorination of atrazine, simazine, and desethylatrazine but is not active with melamine, terbutylazine, or desethyldesisopropylatrazine. Our results indicate that AtzA is a novel atrazine-dechlorinating enzyme with fairly restricted substrate specificity and contributes to the microbial hydrolysis of atrazine to hydroxyatrazine in soils and groundwater.